Penerapan Standar Akuntansi Keuangan Pada Organisasi Nirlaba: Literatur Review - Melia, Yeni (IAIN Kudus, 2022)
This research examines the extent to which the application of Financial Accounting Standards in non-profit organizations. This research uses a literature study analyzed from a review of 102 articles with three methods, namely planning, implementation, and reporting, by producing 28 articles. Then the 28 articles were reviewed using a comparison technique, looking for similarities between several works of literature and concluding. The results of the 28 articles’ review show that non-profit organizations have not yet applied the applicable Financial Accounting Standards in Indonesia. They are still using the cash basis and single entry method of recording due to several constraints, such as limited human resources and knowledge of financial statement preparation. This research is different from previous research because this research is the first to review how the implementation of SAK in non-profit organizations in Indonesia, most of the previous research focused on only one entity, while this research examines how all non-profit organizations (mosques and churches, foundations, Islamic boarding schools, social institutions, orphanages).